Culturally Responsive Pedagogy in Mathematics: Effects on Achievement, Engagement, Perceptions and Attitudes of SHS Students in Ghana - Dookurong Dilor, Isaiah (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
Purpose – This study investigates the influence of Culturally Responsive Pedagogy (CRP) on senior high school students’ achievement, engagement, attitudes, and perceptions in mathematics within the Ghanaian context. CRP, though widely studied in literacy, remains underexplored in mathematics education, particularly in African settings. Methodology – A quasi-experimental design with a non-equivalent groups approach was adopted. A purposive sample of 79 students from Wa Senior High School was divided into control and intervention groups. Over four weeks, the intervention group received mathematics instruction on simultaneous equations using CRP strategies, while the control group was taught with conventional methods. Data were collected through pre- and post-tests, a four-point Likert-type engagement scale, and validated attitude and perception questionnaires (α = 0.74–0.91). Independent sample t-tests were used for analysis. Findings – Results revealed that students exposed to CRP significantly outperformed their peers in mathematics achievement and demonstrated higher levels of behavioral engagement. Participants in the CRP group also reported lessons as more inclusive and culturally relatable, with positive effects on attitudes and perceptions toward mathematics. These findings affirm the potential of CRP to enhance both academic and affective learning outcomes by situating content within students’ sociocultural realities. Novelty – This study extends CRP research into mathematics, providing empirical evidence from an under-researched African context. It highlights how integrating culture into mathematics pedagogy can promote equity, relevance, and learner-centered instruction. Significance – The study is relevant for mathematics teachers, curriculum developers, policymakers, and teacher educators seeking to design inclusive pedagogical approaches that strengthen equity and achievement in mathematics.